Method for modifying polycarboxylate superplasticizer by Ti-SiO2 porous microspheres, modified polycarboxylate superplasticizer and application
By modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres, the spatial steric hindrance and electrostatic repulsion mechanism of nano-Ti-SiO2 are utilized to solve the problem of poor performance of traditional superplasticizers in manufactured sand systems, achieving high-efficiency water reduction, viscosity reduction and slump retention in concrete, and improving the strength and durability of concrete.
Patent Information
- Application Number
- CN202511469408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2026-01-13
AI Technical Summary
Traditional polycarboxylate superplasticizers have limited effectiveness in manufactured sand or low water-cement ratio systems, leading to increased concrete pumping pressure and decreased filling capacity. Furthermore, the lack of a unified definition and performance evaluation standards for viscosity reducers affects construction performance and strength.
Ti-SiO2 porous microspheres are used to modify polycarboxylate superplasticizer. Through the steric hindrance effect and electrostatic repulsion of nano-Ti-SiO2 porous microspheres, the spacing between cement particles is increased, free water is released, a composite adsorption layer is formed, particle agglomeration is prevented, the hydration process is optimized, and the viscosity of the slurry is reduced.
It improves the water reduction rate, slump retention, and compressive strength of concrete, solves the problems of high viscosity and poor retention of traditional water-reducing agents, and enhances the density and durability of concrete.
Smart Images

Figure CN121319296A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of polycarboxylic acid water reducing agent modification, in particular to a method for modifying polycarboxylic acid water reducing agent by Ti-SiO2 porous microspheres, modified polycarboxylic acid water reducing agent and application. BACKGROUND
[0002] Concrete plays an irreplaceable role in infrastructure construction and is widely used in national defense protection, hydropower engineering, bridge and house construction, and plays an important role in the development of national economy. With the rapid development of China's economic society, the demand for concrete in urban and infrastructure construction has increased significantly, and the demand for cement has increased dramatically. With the development of China's infrastructure construction towards high-rise and large-span, concrete materials are evolving towards high-strength and super-high-strength, and low water-binder ratio and high mineral admixture have become the core means to improve strength, but the high viscosity problem caused by this significantly restricts the construction performance. The pumping pressure of such concrete increases dramatically, and the filling property decreases, greatly increasing the difficulty of mixing, transporting and pouring, which becomes a key obstacle to the promotion of high-strength concrete. The scarcity of natural sand resources and the tightening of environmental protection policies promote the widespread replacement of natural sand by machine-made sand, but its characteristics of sharp corners, discontinuous gradation and high stone powder content further exacerbate the viscosity problem of low-grade concrete. Although traditional polycarboxylic acid water reducing agents can improve fluidity, they have limited effect in machine-made sand or low water-binder ratio systems, and need to be significantly increased in dosage, which can easily cause condensation delay, early strength decay and other side effects. The existing viscosity reduction schemes have obvious limitations: air entraining agents reduce viscosity through the "ball bearing effect" but damage strength and durability; viscosity-reducing carboxylic acids have weak effect at ultra-low water-binder ratio; and the effect of admixture gradation optimization on super-high-strength concrete is insufficient. At the same time, the industry lacks a unified definition, classification and performance evaluation standard for viscosity reducers, resulting in chaotic product quality control and restricting engineering applications.
[0003] The role of the high polymer nano material in the cement matrix can be summarized as follows: (1) crystal nucleus effect: the nano particles can act as crystal nucleus in the cement pore solution, promote the deposition of cement hydration products on its surface, and due to its large specific surface area, increase the crystal nucleus site, greatly accelerate the cement hydration process; (2) filling effect: the nano particles can fill the pores in the interface transition zone between the aggregate and the cement paste, and also fill the pores in the internal hydration gel, reduce the porosity of the hardened paste, and improve the compactness; (3) reaction activity: it can react with calcium hydroxide, generate additional hydration gel, increase the total amount of gel in the cement hydration product, and some materials have high strength, toughness and elastic modulus, which can improve the brittleness and cracking performance of the cement-based material itself. SiO2 surface contains more hydroxyl groups, these functional groups show weak acidity, promote the adsorption of calcium ions to the surface of nano SiO2, so that the surface has positive charge, the water reducing agent as an anionic surfactant, is easily adsorbed to the positively charged nano SiO2 surface, improves the slurry fluidity and rheological properties, improves the compressive strength, reduces the porosity, and densifies the matrix. Due to the surface effect of the nano material, its large specific surface area (surface area / volume) will cause the nano material to easily adsorb water, resulting in incomplete filling or delamination, thus reducing the workability of the mixture.
[0004] Therefore, the present application is provided. SUMMARY
[0005] The first object of the present application is to provide a method for modifying polycarboxylic acid water reducer by using nano Ti-SiO2 porous microspheres, which can effectively reduce the surface tension of the slurry, increase the cement particle spacing, release more free water, and further improve the viscosity reduction performance of the cement slurry, the mechanical properties and durability of the hardened cement material, and the strength of the concrete.
[0006] The second object of the present application is to provide a Ti-SiO2 porous microsphere modified polycarboxylic acid water reducer, which can enhance the early strength of the concrete, has better water reducing rate and slump retention performance, can improve the compactness, durability and overall mechanical properties of the concrete, and prevent cement particle agglomeration.
[0007] The third object of the present application is to provide the application of the Ti-SiO2 porous microsphere modified polycarboxylic acid water reducer in the concrete product.
[0008] The fourth object of the present application is to provide a method for reducing the structural viscosity of the cement slurry, which comprises the method of the Ti-SiO2 porous microsphere modified polycarboxylic acid water reducer.
[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: This invention first provides a method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres, comprising the following steps: (a) Preparation of Ti-SiO2 porous microspheres: A composite solution containing Ti-Si was added to a mixture of oil phase compound and surfactant and stirred. Then, under hot water bath conditions, an acid solution was added to adjust to neutrality. After filtration, washing and drying, nano-Ti-SiO2 porous microspheres were obtained. The oil phase compound includes at least one of isooctane, ethanol, and n-hexane; (b) The nano-Ti-SiO2 porous microspheres obtained in step (a), polyether monomers, unsaturated carboxylic acid monomers, initiators, reducing agents and water are mixed and reacted to obtain Ti-SiO2 porous microsphere modified polycarboxylic acid water-reducing agent.
[0010] Further, in step (a), the mass ratio of the oil phase compound to the Ti-Si-containing composite solution is 0.5 to 3:1.
[0011] Further, in step (a), the Ti-Si-containing composite solution is prepared by mixing and reacting a titanium source, a silica sol, and a silane coupling agent.
[0012] Furthermore, the titanium source includes at least one of tetrabutyl titanate, tetraethyl titanate, titanium tetrachloride, and titanium trichloride.
[0013] Furthermore, the silane coupling agent includes at least one of aminosilane, epoxysilane, and thiosilane.
[0014] Further, in step (a), the surfactant includes at least one of Span 85, Tween 80, and Tween 85.
[0015] Further, in step (a), the acid includes at least one of hydrochloric acid, acetic acid, and nitric acid.
[0016] Further, in step (b), the mass ratio of the nano-Ti-SiO2 porous microspheres, the polyether monomer, the unsaturated carboxylic acid monomer, the reducing agent, and the initiator is 5~15:250~350:20~40:0.5~1:1~4.
[0017] Further, the polyether monomer includes methyl allyl polyoxyethylene ether; and / or; the unsaturated carboxylic acid monomer includes at least one of acrylic acid and methacrylic acid.
[0018] Furthermore, the initiator includes at least one of hydrogen peroxide, sodium persulfate, ammonium persulfate, and potassium persulfate; and / or the reducing agent includes at least one of sodium sulfite, sodium dioctyl succinate sulfonate, vitamin C, ferrous sulfate, and E51.
[0019] The present invention further provides a modified polycarboxylate superplasticizer prepared by the method of modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres.
[0020] The present invention also provides a method for reducing the structural viscosity of cement paste, including the method of modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres.
[0021] The present invention also provides an application of the modified polycarboxylate superplasticizer described above in concrete products.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The preparation method of nano-Ti-SiO2 porous microsphere modified polycarboxylate superplasticizer provided by the present invention uses the bimetallic and microporous structure of nano-Ti-SiO2 porous microspheres as a modifier of polycarboxylate superplasticizer. The modified polycarboxylate superplasticizer prepared can make concrete have high water reduction and slump retention performance while also having certain viscosity reduction performance.
[0023] (2) The modified polycarboxylate superplasticizer prepared by the method of modifying polycarboxylate superplasticizer with nano-Ti-SiO2 porous microspheres provided by the present invention has better viscosity reduction and slump retention properties, which improves the workability of concrete and has higher compressive strength. It solves the problems of high viscosity and inability to retain slump in the later stage of traditional superplasticizers. Attached Figure Description
[0024] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0025] Figure 1 This is a schematic diagram illustrating the mechanism of interaction between the titanium-doped silica-modified polycarboxylate superplasticizer and cement provided by the present invention. Figure 2 This is a SEM image of the nano-Ti-SiO2 porous microspheres prepared in Example 1 of the present invention; Figure 3 This is a BET diagram of the nano-Ti-SiO2 porous microspheres prepared in Example 1 of the present invention. Detailed Implementation
[0026] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0027] Unless otherwise specified, in this invention, terms such as "first aspect," "second aspect," "third aspect," and "fourth aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, terms such as "first," "second," "third," and "fourth" serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0028] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0029] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.
[0030] In a first aspect, the present invention provides a method for modifying a polycarboxylate superplasticizer with Ti-SiO2 porous microspheres, comprising the following steps: (a) Preparation of Ti-SiO2 porous microspheres: A composite solution containing Ti-Si was added to a mixture of oil phase compound and surfactant and stirred. Then, under hot water bath conditions, an acid solution was added to adjust to neutrality. After filtration, washing and drying, nano-Ti-SiO2 porous microspheres were obtained. The oil phase compound includes at least one of isooctane, ethanol, and n-hexane; (b) The nano-Ti-SiO2 porous microspheres obtained in step (a), polyether monomers, unsaturated carboxylic acid monomers, initiators, reducing agents and water are mixed and reacted to obtain Ti-SiO2 porous microsphere modified polycarboxylic acid water-reducing agent.
[0031] The present invention provides a method for modifying polycarboxylate superplasticizer with nano-Ti-SiO2 porous microspheres. The bimetallic and microporous structure of nano-Ti-SiO2 porous microspheres is used as a modifier for polycarboxylate superplasticizer. The modified polycarboxylate superplasticizer obtained can make concrete have high water reduction and slump retention performance, while also having a certain viscosity reduction performance.
[0032] Specifically, this invention mainly utilizes the steric hindrance effect, more accessible active sites, and electrostatic repulsion between nano-Ti-SiO2 porous microspheres and polycarboxylate superplasticizers. The main mechanism is that the extremely large specific surface area of nano-Ti-SiO2 makes it easily adsorb surrounding cement particles, increasing the internal pore volume and introducing more free water. This results in surface water forming a water film on the cement particle surface and filling water existing between cement particles. The modified polycarboxylate superplasticizer molecular side chains of the grafted nano-Ti-SiO2 porous microspheres extend into the surrounding solution, forming a three-dimensional barrier that physically prevents particle contact and flocculation, ensuring uniform particle dispersion in the system and reducing "internal friction" caused by agglomeration. Simultaneously, the long side chains of the comb-like structure of polycarboxylate extend towards the outside of the cement, generating repulsion between cement particles and releasing more free water. This increases the dispersibility and fluidity of the slurry, ultimately improving water reduction, viscosity reduction, and slump retention performance. A schematic diagram of this mechanism is shown below. Figure 1 As shown.
[0033] The nano-Ti-SiO2 porous microsphere framework used in this invention is electrically neutral, requiring no ion charge compensation. Its pores preferentially adsorb nonpolar or low-polarity organic molecules, exhibiting hydrophobicity. It possesses a large specific surface area, capable of filling the spaces between particles and displacing internal water, increasing the free water content within the mixture and thus improving slurry fluidity. The reaction mechanism involves the nano-Ti-SiO2 porous material surface being rich in hydroxyl groups (-OH), which can combine with the carboxyl and ether groups of polycarboxylate superplasticizer through hydrogen bonding or coordination to form a "cement particle-polycarboxylate superplasticizer-nano-Ti-SiO2" composite adsorption layer. The thickness of this composite layer is much greater than that of a single polycarboxylate superplasticizer adsorption layer, significantly enhancing the steric hindrance effect and more effectively preventing secondary agglomeration of cement particles. Furthermore, the nano-Ti-SiO2 porous material carries a negative surface charge in alkaline cement slurry (due to Si-O...). - Ti-O - The dissociation of functional groups creates a superposition effect with the negative charge of the polycarboxylate superplasticizer adsorption layer, increasing the absolute value of the ζ potential on the surface of cement particles, enhancing the electrostatic repulsion between particles, reducing the probability of collision aggregation, and thus helping to improve the dispersibility and fluidity of concrete and increase the water reduction rate.
[0034] For aggregates with high mud content, the pores and surface active sites of nano-Ti-SiO2 porous materials can preferentially adsorb clay particles, reducing the "competition" between clay and polycarboxylate superplasticizer, ensuring that the polycarboxylate superplasticizer acts more on cement particles. Simultaneously, nano-Ti-SiO2 porous materials can fill the micro-voids between cement particles (particle size 1~100μm), reducing "voids" in the slurry, making the particles more compact and uniform, and reducing the "jamming" effect between particles (similar to how adding fine stones to sand reduces friction); the porous structure can also adsorb some Ca. 2+ Reduce the Ca content in the slurry 2+ Concentration slows down the formation rate of ettringite and CSH gel, reduces the bridging effect of early hydration products on particles, and maintains the low viscosity of the slurry. Nano-Ti-SiO2 acts as a nucleation site, inducing preferential growth of CSH gel on its surface, forming short rod-shaped or flocculent fine hydration products, preventing the hydration products from intertwining and forming a "rigid skeleton," thereby reducing the structural viscosity of the slurry. Through the synergistic effect of multiple mechanisms—enhanced dispersion repulsion, optimized particle size distribution, slow-release water-reducing agent, and regulation of hydration process—the flocculation structure of the cement slurry is fundamentally destroyed, interparticle friction is reduced, and slurry fluidity is maintained, achieving a significant viscosity reduction effect.
[0035] Under alkaline conditions, the Ti-O-Si bonds are linked to the polycarboxylic acid molecule backbone through the carboxyl groups (-COO). - The metal ions (especially Ca) released by the hydration reaction 2+ The synergistic effect of forming stable complexes and steric hindrance makes the Ca in the solution... 2+ The decrease in concentration hinders the precipitation of calcium hydroxide (CH) and the formation of ettringite (AFt), thereby prolonging the workability of concrete. This invention utilizes nano-Ti-SiO2 porous microspheres, which are adsorbed on the surface of cement particles and release more comb-like structures. During hydrolysis, a large number of carboxyl groups (-COOH) are generated, making them more negatively charged. Through the principle of "like charges repel" between molecules, particles are prevented from approaching each other and agglomerating, thus improving workability and slowing down the cement hydration process, thereby improving the slump retention of concrete.
[0036] Therefore, the polycarboxylate superplasticizer modified with nano-Ti-SiO2 porous microspheres prepared in this invention has better water-reducing, viscosity-reducing, and slump-retaining properties, improving the workability of concrete and giving it higher compressive strength. It solves the problems of high viscosity and poor slump retention found in traditional superplasticizers.
[0037] In some specific implementations, as an example, the preparation method of Ti-SiO2 porous material microspheres specifically includes: After mixing and stirring the Ti-Si composite solution, oil phase compound and surfactant for 2 hours, the mixture was quickly transferred to a hot water bath and stirred for 10 minutes. Then, an appropriate amount of acid was added to adjust the pH to neutral. The obtained Ti-SiO2 material was filtered and separated. The solvent and surfactant on the surface were washed away by alternating washing with anhydrous ethanol and water, and then dried to obtain the Ti-SiO2 porous microspheres.
[0038] In some specific embodiments, an oil phase compound and a surfactant are first used to prepare a microemulsion, which is then mixed with a Ti-Si composite solution. The preparation method of the microemulsion includes: mixing the oil phase compound and the surfactant and stirring at a speed of 1000-1500 rpm until the solution is clear.
[0039] In some specific implementations, the temperature of the hot water bath is 60~100℃, including but not limited to 60℃, 70℃, 80℃, 90℃, and 100℃.
[0040] In some specific embodiments, the mass ratio of the oil phase compound to the Ti-Si-containing composite solution is 0.5 to 3:1, for example, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, or 3:1. Using the above-mentioned amount of oil phase compound can ensure the stability of the porous structure of nano-Ti-SiO2 and the appropriate pore size.
[0041] In some specific implementations, as an example, step (b) specifically includes: Polyether monomers, unsaturated carboxylic acid monomers, and reducing agents are dissolved in water to obtain polyether monomer solutions, unsaturated carboxylic acid monomer solutions, and reducing agent solutions, respectively. The polyether monomer solution is mixed evenly with an initiator and nano-Ti-SiO2 porous microspheres obtained in step (a). Then, the unsaturated carboxylic acid monomer solution and the reducing agent solution are added dropwise to the mixture. After the addition is complete, the reaction is carried out for 1 to 4 hours (e.g., 2 hours, 2.5 hours, or 3 hours). Then, an alkaline solution is added to the reaction system to adjust the pH to 7 to 8 (e.g., 7.1, 7.3, 7.6, or 7.9).
[0042] In some specific implementations, the dropwise addition time of the unsaturated carboxylic acid monomer solution is 1 to 3 hours.
[0043] In some specific implementations, the reducing agent solution is added dropwise over a period of 1 to 3 hours.
[0044] In some specific implementations, the reaction temperature after the addition is completed is the room temperature, such as 15~25°C, but not limited to this.
[0045] In some specific embodiments, the alkaline solution includes at least one of NaOH solution and KOH solution, but is not limited thereto.
[0046] In a preferred embodiment, the drying method includes at least one of freeze drying, vacuum drying, and spray drying.
[0047] In some specific embodiments, in step (a), the Ti-Si-containing composite solution is prepared by mixing and reacting a titanium source, a silica sol, and a silane coupling agent. The titanium source includes at least one of n-butyl titanate, tetraethyl titanate, titanium tetrachloride, and titanium trichloride. The silane coupling agent includes at least one of aminosilane, epoxysilane, and thiosilane.
[0048] As an example, the preparation method of the Ti-Si composite solution can be completed by the following steps: After mixing and stirring the titanium source and silica sol, the mixture is frozen to a slushy state, then stirred and thawed. The freezing-thawing process is repeated at least three times. The silane coupling agent is then added, and the mixture is stirred at 60-100°C for 4-12 hours.
[0049] In some specific embodiments, in step (a), the surfactant includes at least one of Span 85, Tween 80, and Tween 85.
[0050] In some specific embodiments, in step (a), the acid includes at least one of hydrochloric acid, acetic acid, and nitric acid.
[0051] In some specific embodiments, in step (b), the mass ratio of nano-Ti-SiO2 porous microspheres, polyether monomers, unsaturated carboxylic acid monomers, reducing agent, and initiator is 5-15 (e.g., 5, 8, 10, 12, or 15): 250-350 (e.g., 270, 285, 300, 330, or 340): 20-40 (e.g., 28, 28, 30, 32, 35, or 37): 0.5-1 (e.g., 0.5, 0.6, 0.7, 0.8, or 0.9): 1-4 (e.g., 1.2, 2.2, 2.8, 3.2, or 3.8). Using this ratio can improve water reduction and slump retention performance.
[0052] In some specific embodiments, the polyether monomer includes methyl allyl polyoxyethylene ether. The unsaturated carboxylic acid monomer includes at least one of acrylic acid and methacrylic acid. The initiator includes at least one of hydrogen peroxide, sodium persulfate, ammonium persulfate, and potassium persulfate. The reducing agent includes at least one of sodium sulfite, sodium dioctyl succinate sulfonate, vitamin C, ferrous sulfate, and E51.
[0053] Secondly, the present invention provides a modified polycarboxylate superplasticizer prepared by a method of modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres.
[0054] Thirdly, the present invention provides an application of a modified polycarboxylate superplasticizer in concrete products.
[0055] Fourthly, the present invention provides a method for reducing the structural viscosity of cement paste, including a method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres.
[0056] The polycarboxylate superplasticizer modified with nano-Ti-SiO2 porous microspheres prepared by this invention can enhance the viscosity reduction performance of concrete, and has better water reduction rate and slump retention performance. It can improve the density, durability and overall mechanical properties of concrete, and also prevent cement particle agglomeration. It can be used to produce various concrete products and has a wide range of applications in construction, transportation, water conservancy, agriculture, power and other fields.
[0057] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0058] Example 1 The preparation method of the nano-Ti-SiO2 porous microsphere modified polycarboxylate superplasticizer provided in this embodiment includes the following steps: (1) Preparation of Ti-Si composite solution: TBT alcohol solution was obtained by mixing tetrabutyl titanate and anhydrous ethanol at a mass ratio of 1:2.5 and stirring for 30 min. The TBT alcohol solution was slowly added dropwise to 100 g of silica sol (SiO2 content of 30 wt.%) at a molar ratio of titanium to silicon of 1:1. After stirring for 1 h, it was placed in a -40℃ environment and frozen to a slushy state. The mixture was then physically stirred and thawed, and the freezing-thawing process was repeated 3 times to obtain a titanium-silicon mixture. The titanium-silicon mixture was slowly poured into 0.75 g of KH550 silane coupling agent (i.e., the mass ratio of silane coupling agent to silica sol was 0.75:100) and stirred at 80℃ for 4 h. After cooling to room temperature, a titanium-doped silica solution was obtained.
[0059] (2) Isooctane and the Ti-Si composite solution with a mass ratio of 0.5:1 were placed in a three-necked flask and stirred at room temperature for 2 hours. 100g of Span 85 (surfactant) was added and stirred for 2 hours. The flask was then placed in an environment of 100℃ and stirred for 10 minutes. An appropriate amount of 1M hydrochloric acid was added to the solution to adjust it to neutral to obtain Ti-SiO2 material. The solvent and surfactant on the surface were washed away by alternating washing with anhydrous ethanol and water. The solution was then freeze-dried for 12 hours and restored to room temperature to obtain nano-Ti-SiO2 porous microspheres. Figure 2 This is a SEM image of the nano-Ti-SiO2 porous microspheres prepared in Example 1 of this invention; Figure 3 This is a BET diagram of the nano-Ti-SiO2 porous microspheres prepared in Example 1.
[0060] (3) Weigh 300g of methyl allyl polyoxyethylene ether and 58 parts of deionized water into a four-necked flask to prepare bottom solution A. Weigh 30g of acrylic acid and 30 parts of deionized water into a beaker to prepare material B. Weigh 0.7g of E51 and 50 parts of deionized water into a beaker to prepare material C. At room temperature (25℃), add 10g of nano-Ti-SiO2 porous microspheres obtained in step (1), 2.5g of hydrogen peroxide and 2.5g of ammonium persulfate to the prepared bottom solution A. After stirring for 8min, add the prepared materials B and C dropwise at a uniform rate. The dropwise addition time for material B is 2h and the dropwise addition time for material C is 2.5h. After the addition is completed, continue the reaction for 1 hour. Then adjust the pH value of the reaction system to 7 with NaOH solution to obtain the polycarboxylate superplasticizer modified with nano-Ti-SiO2 porous microspheres.
[0061] Example 2 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (1), the corresponding amount of the composite solution containing Ti-Si is added to 500g of isooctane according to the mass ratio of the oil phase compound to the composite solution containing Ti-Si being 1:1.
[0062] Example 3 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (1), the corresponding amount of the Ti-Si-containing composite solution is added to 500g of isooctane according to the mass ratio of the oil phase compound to the Ti-Si-containing composite solution being 1.5:1.
[0063] Example 4 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (1), the corresponding amount of the Ti-Si-containing composite solution is added to 500g of isooctane according to the mass ratio of the oil phase compound to the Ti-Si-containing composite solution being 2:1.
[0064] Example 5 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (1), the corresponding amount of the Ti-Si-containing composite solution is added to 500g of isooctane according to the mass ratio of the oil phase compound to the Ti-Si-containing composite solution being 2.5:1.
[0065] Example 6 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (1), the corresponding amount of the Ti-Si-containing composite solution is added to 500g of isooctane according to the mass ratio of the oil phase compound to the Ti-Si-containing composite solution being 3:1.
[0066] Example 7 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (1), the mass of isooctane is replaced with 5000g (that is, the mass ratio of isooctane to the composite solution containing Ti-Si is 20:1).
[0067] Example 8 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (2), acrylic acid is replaced with an equal mass of methacrylic acid.
[0068] Example 9 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (2), the initiator ammonium persulfate is removed, hydrogen peroxide is replaced with an equal mass of ammonium persulfate, and E51 is replaced with an equal mass of ferrous sulfate.
[0069] Example 10 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (2), ammonium persulfate is replaced with an equal mass of sodium persulfate, and E51 is replaced with an equal mass of vitamin C.
[0070] Example 11 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (2), the mass of Span 85 is replaced with 120g.
[0071] Example 12 The preparation method of the modified polycarboxylate superplasticizer provided in this embodiment is basically the same as that in Example 1. The difference is that in step (2), except for the solvent water, the mass of each raw material is as follows: 350g methyl allyl polyoxyethylene ether, 40g acrylic acid, 1g E51, 10g nano Ti-SiO2 porous microspheres and 4g hydrogen peroxide (hydrogen peroxide concentration is the same as in Example 1).
[0072] Comparative Example 1 The preparation method of the polycarboxylate superplasticizer provided in this comparative example is basically the same as that in Example 1, except that step (1) is not performed and nano Ti-SiO2 porous microspheres are not added in step (2).
[0073] Comparative Example 2 The preparation method of the polycarboxylate superplasticizer provided in this comparative example is basically the same as that in Example 1, except that step (1) is not performed, and in step (2) the nano-Ti-SiO2 porous microspheres are replaced with commercially available porous silica material of equal mass.
[0074] Comparative Example 3 The polycarboxylate superplasticizer provided in this comparative example is a commercially available viscosity-reducing polycarboxylate superplasticizer from a certain company.
[0075] Comparative Example 4 The preparation method of the polycarboxylate superplasticizer provided in this comparative example is basically the same as that in Example 1, except that in step (2), the mass of nano Ti-SiO2 porous microspheres is replaced with 15g.
[0076] Comparative Example 5 The preparation method of the polycarboxylate superplasticizer provided in this comparative example is basically the same as that in Example 1. The difference is that in step (2), nano-Ti-SiO2 porous microspheres are replaced with titanium-doped silicon dioxide of equal mass.
[0077] Experimental Example According to the requirements of GB / T8077-2023 "Test Method for Homogeneity of Concrete Admixtures", cement, water and nano-Ti-SiO2 porous microsphere modified polycarboxylate superplasticizer (or polycarboxylate superplasticizer) were mixed. The mortar performance of the nano-Ti-SiO2 porous microsphere modified polycarboxylate superplasticizers prepared in each example was compared with the polycarboxylate superplasticizers in each comparative example. The results are shown in Table 1.
[0078] Table 1 Results of water reduction rate for each group
[0079] Referring to Table 1 and Examples 1-6, the water reduction rate increases with the increase of the ratio of oil phase compound to Ti-Si composite liquid. The water reduction rate results show that the rate gradually increases with the increase of the ratio. When the ratio is 2:1 (Example 4), the water reduction rate reaches a peak of 30.25%, and then decreases. This is because the higher proportion of oil phase compound inhibits the formation of long silicon-titanium bonds, resulting in smaller particle size of the synthesized nano-Ti-SiO2 porous microspheres. These microspheres essentially become fillers between cement particles, failing to expand the surface and failing to meet the coordination requirements of active sites. This is also evidenced by the data in Example 7, where the water reduction rate decreases with the increase of the ratio of oil phase compound to Ti-Si composite liquid. Furthermore, when the ratio of oil phase compound to Ti-Si composite liquid remains constant, changing the components and proportions in the formulation (Examples 8-12) leads to a decrease in the water reduction rate.
[0080] Comparing the modified polycarboxylate superplasticizers prepared in this invention (Examples 1-6) with ordinary polycarboxylate superplasticizers (Comparative Example 1), commercial silica-modified polycarboxylate superplasticizers (Comparative Example 2), and commercially available polycarboxylate superplasticizers (Comparative Example 3), it can be seen that the nano-Ti-SiO2 porous microsphere-modified polycarboxylate superplasticizers prepared in this invention (Examples 1-6) all have high water reduction rates; while increasing the amount of nano-Ti-SiO2 porous microspheres in Example 4 (Comparative Example 4) did not significantly increase the water reduction rate. Therefore, the nano-Ti-SiO2 porous microsphere-modified polycarboxylate superplasticizers prepared in this invention have high water reduction rates.
[0081] The nano-Ti-SiO2 porous microsphere modified polycarboxylate superplasticizers prepared in the above embodiments were compared with the polycarboxylate superplasticizers in the comparative examples in concrete performance testing. The testing methods were carried out in accordance with the methods specified in GB / T50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". Concrete was Conch P.O42.5 cement. The C50 concrete test mix is shown in Table 2 below, and the scalability and compressive strength properties are shown in Table 3.
[0082] Table 2 Concrete mix proportions (kg / m³) 3 )
[0083] Table 3 Concrete performance of various polycarboxylate superplasticizers (constituent dosage: 0.16%)
[0084] As shown in Table 3, when the total admixture content is 0.16%, compared with polycarboxylate superplasticizer, commercially available superplasticizer, and silica-modified superplasticizer (Comparative Examples 1-3), the nano-Ti-SiO2 porous microsphere-modified polycarboxylate superplasticizers (Examples 1-6) prepared in each embodiment of the present invention have better workability, slump retention, and viscosity reduction properties, and also have higher compressive strength at 3 days (3d) and 28 days (28d). Increasing the amount of nano-Ti-SiO2 porous microsphere-modified polycarboxylate superplasticizer (Comparative Example 4) does not significantly improve workability and viscosity reduction. Although the titanium-doped silica solution-modified polycarboxylate superplasticizer (Comparative Example 5) has a higher water reduction rate, the Ti-SiO2 porous microsphere-modified polycarboxylate superplasticizer of this embodiment has greater advantages in concrete workability, viscosity reduction properties, and compressive strength at 3 days and 28 days.
[0085] In summary, the modified polycarboxylate superplasticizer prepared by the method of modifying polycarboxylate superplasticizer with nano-Ti-SiO2 porous microspheres provided by the present invention has a higher water reduction rate, workability and slump retention, improved mechanical strength and durability, and significantly improved viscosity reduction performance.
[0086] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. A method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres, characterized in that, Includes the following steps: (a) Preparation of Ti-SiO2 porous microspheres: A composite solution containing Ti-Si was added to a mixture of oil phase compound and surfactant and stirred. Then, under hot water bath conditions, an acid solution was added to adjust to neutrality. After filtration, washing and drying, nano-Ti-SiO2 porous microspheres were obtained. The oil phase compound includes at least one of isooctane, ethanol, and n-hexane; (b) The nano-Ti-SiO2 porous microspheres obtained in step (a), polyether monomers, unsaturated carboxylic acid monomers, initiators, reducing agents and water are mixed and reacted to obtain Ti-SiO2 porous microsphere modified polycarboxylic acid water-reducing agent.
2. The method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres according to claim 1, characterized in that, In step (a), the Ti-Si-containing composite solution is prepared by mixing and reacting a titanium source, silica sol, and a silane coupling agent; Preferably, the titanium source includes at least one selected from tetrabutyl titanate, tetraethyl titanate, titanium tetrachloride, and titanium trichloride; Preferably, the silane coupling agent includes at least one of aminosilane, epoxysilane, and thiosilane.
3. The method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres according to claim 1, characterized in that, In step (a), the surfactant includes at least one of Span 85, Tween 80, and Tween 85; and / or the acid includes at least one of hydrochloric acid, acetic acid, and nitric acid.
4. The method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres according to claim 1, characterized in that, In step (a), the mass ratio of the oil phase compound to the Ti-Si-containing composite solution is 0.5 to 3:
1.
5. The method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres according to any one of claims 1 to 4, characterized in that, In step (b), the mass ratio of the nano-Ti-SiO2 porous microspheres, the polyether monomer, the unsaturated carboxylic acid monomer, the reducing agent, and the initiator is 5~15:250~350:20~40:0.5~1:1~4.
6. The method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres according to claim 5, characterized in that, The polyether monomer includes methyl allyl polyoxyethylene ether; and / or; the unsaturated carboxylic acid monomer includes at least one of acrylic acid and methacrylic acid.
7. The method for modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres according to claim 5, characterized in that, The initiator includes at least one of hydrogen peroxide, sodium persulfate, ammonium persulfate, and potassium persulfate; and / or the reducing agent includes at least one of sodium sulfite, sodium dioctyl succinate sulfonate, vitamin C, ferrous sulfate, and E51.
8. The modified polycarboxylate superplasticizer prepared by the method of modifying polycarboxylate superplasticizer with Ti-SiO2 porous microspheres as described in any one of claims 1 to 7.
9. The application of the modified polycarboxylate superplasticizer as described in claim 8 in concrete products.
10. A method for reducing the structural viscosity of cement paste, characterized in that, The method includes the Ti-SiO2 porous microsphere modified polycarboxylate superplasticizer as described in any one of claims 1 to 7.